Myelin water imaging in relapsing multiple sclerosis treated with ocrelizumab and interferon beta-1a - Shannon Kolind; Shawna Abel; Carolyn Taylor; Roger Tam; Cornelia Laule; David K.B. Li; Hideki Garren; Laura Gaetano; Corrado Bernasconi; David Clayton; Irene Vavasour; Anthony Traboulsee (NeuroImage: Clinical, 2022)
Background: Myelin water imaging is a magnetic resonance imaging (MRI) technique ﻿that quantifies myelin damage and repair in multiple sclerosis (MS) via the myelin water fraction (MWF). Objective: In this substudy of a phase 3 therapeutic trial, OPERA II, MWF was assessed in relapsing MS participants assigned to interferon beta-1a (IFNb-1a) or ocrelizumab (OCR) during a two-year double-blind period (DBP) followed by a two-year open label extension (OLE) with ocrelizumab treatment. Methods: MWF in normal appearing white matter (NAWM), including both whole brain NAWM and 5 white matter structures, and chronic lesions, was assessed in 29 OCR and 26 IFNb-1a treated participants at weeks 0, 24, 48 and 96 (DBP), and weeks 144 and 192 (OLE), and in white matter for 23 healthy control participants at weeks 0, 48 and 96. Results: Linear mixed-effects models of data from baseline to week 96 showed a difference in the change in MWF over time favouring ocrelizumab in all NAWM regions. At week 192, lesion MWF was lower for participants originally randomised to IFNb-1a compared to those originally randomised to OCR. Controls showed no change in MWF over 96 weeks in any region. Conclusion: Ocrelizumab appears to protect against demyelination in MS NAWM and chronic lesions and may allow for a more permissive micro environment for remyelination to occur in focal and diffusely damaged tissue.